2020
DOI: 10.1038/s41467-020-19221-x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of DNA repair factors ASCC2 and ASCC3 is affected by somatic cancer mutations

Abstract: The ASCC3 subunit of the activating signal co-integrator complex is a dual-cassette Ski2-like nucleic acid helicase that provides single-stranded DNA for alkylation damage repair by the α-ketoglutarate-dependent dioxygenase AlkBH3. Other ASCC components integrate ASCC3/AlkBH3 into a complex DNA repair pathway. We mapped and structurally analyzed interacting ASCC2 and ASCC3 regions. The ASCC3 fragment comprises a central helical domain and terminal, extended arms that clasp the compact ASCC2 unit. ASCC2–ASCC3 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…9b, c ). This domain of Cue3 is similar to the X-ray structure of the human homolog ASCC2 in complex with the N-terminal domain of ASCC3 (Slh1) which we do not observe 37 . The predicted ubiquitin-binding CUE domain (298-360), a linked four-helix bundle (468-541), and the ultimate C-terminus (542-624) are not visible in our structures, most likely due to their high flexibility.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…9b, c ). This domain of Cue3 is similar to the X-ray structure of the human homolog ASCC2 in complex with the N-terminal domain of ASCC3 (Slh1) which we do not observe 37 . The predicted ubiquitin-binding CUE domain (298-360), a linked four-helix bundle (468-541), and the ultimate C-terminus (542-624) are not visible in our structures, most likely due to their high flexibility.…”
Section: Resultssupporting
confidence: 70%
“…9a ). In agreement with this, a contribution of both cassettes was shown for DNA unwinding activity of the human homolog ASCC3 43 , although earlier studies assigned this activity to either the N− 37 or the C-terminal cassette 44 . Since we found that single Walker mutations in both the NTC and the CTC abolish RQT activity (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…ASCC3 contains two Ski2-like helicase domains, but only the N-terminal domain is active ( Jia et al., 2020 ). Since RNA helicases are ATP-gated RBPs, we investigated the link between ASCC3 RNA binding and helicase activity.…”
Section: Resultsmentioning
confidence: 99%
“…The GKT motif in the N-terminal helicase domain of ASCC3 is essential for ATP binding and RNA-helicase activity ( Jia et al., 2020 ). Therefore, we mutated the N-terminal GKT motif and determined the effect on ASCC3 RNA binding in vivo ( Figure 1 E).…”
Section: Resultsmentioning
confidence: 99%
“…Hotspot mutations of SF3B1 are associated with cancer and affect alternative splicing by promoting alternative branchpoint usage [ 53 ]. The affinity between DNA repair factors ASCC2 and ASCC3 is reduced by cancer mutations [ 54 ]. Depletion of SNRPE or SNRPD1 led to autophagy and a marked reduction of cell viability in breast, lung, and melanoma cancer cell lines, accompanied by a deregulation of the mTOR pathway [ 55 ].…”
Section: Resultsmentioning
confidence: 99%